IoT-Based Campus Parking Slot Monitoring System via Ultrasonic Sensors with Real-Time Web Visualization - Prima Miftakhul Rahma; Rendy Syahputra Riyadi; Shofie Ardhya Shafina; Restu Mahardika; Azis Suroni (Journal of INISTA, 2026)
This research develops a campus parking slot monitoring system based on the Internet of Things (IoT) using the HC-SR04 ultrasonic sensor and the ESP32 DevKitC V4 module. The goal is to overcome parking space limitations by providing real-time information on slot availability thru an OLED display and web interface. The system is designed using a prototype development method consisting of ultrasonic sensors to detect vehicle distance, servo motors to operate automatic gates, and ESP32 as a processor and wireless data transmitter. The data from the sensor readings is processed to determine the status of the parking slots and communicated in real-time to the server. OLED displays real-time status on-site, while the web interface shows the overall parking conditions. The test results show the system is capable of detecting the presence of vehicles with high accuracy and stable data communication without significant delay. This system effectively improves parking space search efficiency and reduces congestion in the campus area. Its implementation supports the smart campus concept thru the digitalization of user-friendly, efficient, and scalable parking facility management, which can be developed into a data analysis-based system for smart parking management in the future.